PEX syndrome : Clinical diagnosis and systemic manifestations - Scharfenberg, E.; Schlötzer-Schrehardt, Ursula (Ophthalmologe, 2012)
As a result of demographic changes pseudoexfoliation (PEX) syndrome, an age-related systemic disorder of the extracellular matrix, will become an increasingly important issue in clinical practice. Apart from its well-known association with cataract and glaucoma, PEX syndrome predisposes to a broad spectrum of spontaneous and surgical ocular complications due to characteristic alterations of all anterior segment tissues. In view of the high risk of glaucoma development and potential complications during cataract surgery, an accurate and early diagnosis of PEX syndrome is of considerable clinical relevance. Since the characteristic central PEX deposits are lacking in up to 50 % of patients, a reliable diagnosis requires pupillary dilation. Early stages of the disease may be recognized on the basis of subtle alterations of the lens surface in addition to poor pupillary dilation and pigment-related signs including pigment dispersion and peripupillary atrophy. Any asymmetric clinical signs, e.g., regarding pupil width, pigmentation, cataract and intraocular pressure, should alert the ophthalmologist to the potential presence of PEX syndrome. Although the description of PEX syndrome as a systemic disorder of the extracellular matrix associated with the deposition of PEX material in the skin, blood vessel walls and various organ systems dates back to the early 1990s, a causal relationship between the abnormal material deposits and systemic diseases has not yet been clearly established. A growing number of smaller studies have found suggestive evidence for associations between PEX syndrome and cardiovascular/cerebrovascular diseases. The current evidence, however, is ambiguous and requires further investigation through multicenter or population-based, prospective, randomized clinical studies.
EVALuna2:21100